Isolated renal hydatid cyst managed by laparoscopic transperitoneal nephrectomy - Kartik J Shah; Arvind P Ganpule; Mahesh R Desai (Indian Journal of Urology, 2009)
Hydatid disease is a cyclozoonotic parasitic infestation caused by the cestode Echinococcus granulosus. Isolated renal involvement is extremely rare. A 45-year-old female, working as a farmer, presented with vague abdominal pain and hydatiduria. Ultrasonography of the abdomen revealed hydatid cyst arising from the right kidney. Computerized tomography scan of the abdomen confirmed the findings. Laparoscopic transperitoneal nephrectomy was performed. Isolated right renal hydatid cyst was removed in toto. Microscopic examination confirmed the diagnosis of hydatid cyst. Transperitoneal laparoscopic approach gives a better working space which helped us to remain outside Gerota′s fascia and prevent subsequent cyst rupture.